Loss of interneurons and disruption of perineuronal nets in the cerebral cortex following hypoxia-ischaemia in near-term fetal sheep. Issue 1 (December 2018) - Fowke, Tania; Galinsky, Robert; Davidson, Joanne; Wassink, Guido; Karunasinghe, Rashika; Prasad, Jaya; Bennet, Laura; Gunn, Alistair; Dean, Justin
Abstract Hypoxia-ischaemia (HI) in term infants is a common cause of brain injury and neurodevelopmental impairment. Development of gamma-aminobutyric acid (GABA)ergic circuitry in the cerebral cortex is a critical event in perinatal brain development. Perineuronal nets (PNNs) are specialised extracellular matrix structures that surround GABAergic interneurons, and are important for their function. Herein, we hypothesised that HI would reduce survival of cortical interneurons and disrupt PNNs in a near-term fetal sheep model of global cerebral ischaemia. Fetal sheep (0.85 gestation) received sham occlusion (n = 5) or 30 min of reversible cerebral ischaemia (HI group; n = 5), and were recovered for 7 days. Expression of interneurons (glutamate decarboxylase [GAD]+ ; parvalbumin [PV]+ ) and PNNs (Wisteria floribunda agglutinin, WFA) was assessed in the parasagittal cortex by immunohistochemistry. HI was associated with marked loss of both GAD+ and PV+ cortical interneurons (all layers of the parasagittal cortex and layer 6) and PNNs (layer 6). The expression and integrity of PNNs was also reduced on surviving GAD+ interneurons. There was a trend towards a linear correlation of the proportion of GAD+ neurons that were WFA+ with seizure burden (r2 = 0.76, p = 0.0534). Overall, these data indicate that HI may cause deficits in the cortical GABAergic system involving loss of interneurons and disruption of PNNs, which may contribute to the range of adverse neurological outcomes following perinatal brain injury.